PENINGKATAN KETERAMPILAN MEMBACA MELALUI MEDIA KARTU KATA BERBASIS POWERPOINT PADA ANAK KELOMPOK B DI TK AULIA SAMATA, KABUPATEN GOWA - Dewi, Asra; Asis, Asyriyah; Rauf, St. Muthia; Ilyas, Nurhidayah; Herlina (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
Early reading skills are a fundamental component of early childhood education. This study aimed to improve the early reading skills of Group B kindergarten students at TK Aulia Samata, Gowa Regency by using PowerPoint based word card media to improve letter recognition, phonemic awareness, and phoneme-grapheme correspondence. The study presented a multimedia supported method intended to engage children through interactive and graphically enriched content, acknowledging the shortcomings of traditional training. Three classroom sessions were used in a single cycle of the study, which used the Classroom Action Research (CAR) approach. PowerPoint presentations with animated word cards, visual cues, and auditory reinforcement that complemented the curriculum's thematic content were incorporated into each session. Four literacy indicators were used to gauge students progress through observations and performance evaluations using standardized rubrics.With 66.6% of participants achieving the "Developed as Expected" level by the conclusion of the cycle, the results showed a significant improvement in the reading skills of the children. Students abilities to associate letter symbols with sounds and recognize the first phonemes of words they were familiar with showed the biggest improvements. In conclusion, word card media based on PowerPoint was found to be a useful tool for encouraging the development of early reading skills. The results indicate wider applicability in a variety of educational contexts and emphasize the pedagogical benefits of integrating easily accessible digital resources into literacy instruction. This method emphasizes the value of interactive, child-centered learning environments while providing a workable, affordable way to improve early reading.